A comparison of offending trajectories in violent youth according to violence type. (14th July 2015) - Ching, Hannah; Daffern, Michael; Thomas, Stuart
ABSTRACT: Background: Widespread public concern about youth violence persists, particularly the so‐called acts of appetitive violence characterised by positive affect and exemplified in modern trends such as 'happy slapping'. Empirical research into this phenomenon is scant. Aim: The aim of this study was to determine whether perpetration of appetitive violence signals a specific offending trajectory. Method: We reviewed reports and related material from 105 violent young offenders referred to court mental health services in the state of Victoria, Australia. Index violent offences were categorised as appetitive or not. Official police records were used to determine rearrest during the 12 months following mental health assessment. Results: The nine young people whose offence was classified as appetitive were male and did not reoffend, generally or violently, at different rates than the other youths. Conclusion: The offending trajectories of young people with appetitively violent index offences were indistinguishable from other violent youths. There is thus insufficient information here to recommend distinctive intervention for this subgroup, but their high reoffending rate (7/9) suggests that they are worthy of more research attention. Copyright © 2015 John Wiley & Sons, Ltd.